(untitled) (Scientific journal of the Fergana State University, 2024)
Analysis of the concept of the soul in modern Western philosophy and Alfred Adler’s views on the concept of the soul, love, benevolence, friendship, benevolent, proportionate, disinterested human, moral, research of human creative possibilities as a result of the origin of relationships. Also, the problems of social upliftment of the human heart are covered based on the approaches of modern western philosophy.